Harmonization of Positive Law and Islamic Law in Handling Election Violations in Jambi - Sahroni, Iron; Al Idrusiah, Rahmi Hidayati; Maryani, Maryani; Madjid, M. Nazori; Farhan HR, Muhammad (Journal of Progressive Law and Legal Studies, 2025)
This study aims to examine the forms of criminal violations of the General Election that occurred in Jambi Province during the 2024 Election, and analyze them from the perspectives of positive law and Islamic criminal law. This study uses a qualitative method with an empirical juridical approach, combining literature studies and field data from the Elections Supervisory Agency (Bawaslu), the Law Enforcement Agency (Gakkumdu), and court decisions. The results indicate that the most prevalent violations are money politics, off-schedule campaigning, violations of the neutrality of civil servants (ASN), the Indonesian National Armed Forces (TNI), and the Indonesian National Police (Polri), the spread of hoaxes, vote rigging, and the destruction of campaign materials. Of the total findings and reports in Jambi Province, the majority are administrative violations. However, seven cases were processed as election crimes, some of which have reached the investigation stage and court decisions. From an Islamic criminal law perspective, these violations are categorized as ta'zir crimes, with discretionary sanctions intended to provide a deterrent effect and safeguard the public interest. This study emphasizes the synergy between positive law and Islamic values ​​in realizing honest, fair, and dignified elections.